Application Of Consumption Method With Eoq, Mmsl Forecasting And Abc-Ven Analysis In Pharmaceutical Briefing Management In Hospitals General Royal Prima Marelan - Afni Kartika, Ajeng; Girsang, Ermi; Wienaldi, Wienaldi; Novalinda Ginting, Chrismis (International Journal of Science, Technology & Management, 2023)
Hospitals should plan for drug needs using accountable methods to avoid empty drugs. Good drug planning can improve pharmaceutical stock control in hospitals. The purpose of this study was to find out about the application of consumption methods with EOQ, MMSL and ABC-VEN forecasting in the management of pharmaceutical supplies in hospitals. This study used retrospective mix-method data, quantitative data and qualitative primary data. The research was conducted at RSU Royal Prima Marelan. The results showed that drug supply control using the EOQ method of getting drugs reordered: cefixime 200MG ordered at 447, ondacetron 4MG 740, gabapentin 300MG 706, ranitidine 25MG 1467, novorapid flexpen / 5" 42. In the SS method, the number of drugs available at delivery, cefixime 200MG should be 627 drugs at the time of shipment, ondacetron 4MG should be 522, gabapentin 300MG should be 470, ranitidine 25MG should be 940, and novorapid flexpen/5" should be 26. In the ROP method the drug was reordered at cefixime 200MG it was reordered when the stock was 447 and the quantity ordered was 12027, ondacetron 4MG 740 and 10000, gabapentin 300MG 706 and 9020, ranitidine 25MG 1467 and 18040, novorapid flexpen 42 and 502. In the ABC method, group A as many as 59 types 70.59% with a total investment of 70.59% drug use and an investment value of IDR 606,511,106, group B 64 drug investment 20.33% investment 20.33% drug use investment 174,722,327, group C 146 types (9.08%) investment 9.08% drug use and investment 78,028,263.